Dietary intake and serum concentrations of vitamin A and vitamin E and pre-eclampsia risk in Chinese pregnant women: A matched case-control study - Liu, Yanhua; Ma, Shunping; Huang, Xuemin; Bo, Yacong; Fu, Wenjun; Cao, Yuan; Duan, Dandan; Dou, Weifeng; Zeng, Fangfang; Wang, Xinyi; Gong, Meiyuan; Zhang, Xueyang; et al. (Frontiers in Nutrition, 2023)
Background Many studies have suggested that the serum concentrations of vitamin A (VA) and vitamin E (VE) influence preeclampsia (PE) risk in pregnant women. However, few studies have assessed whether dietary intake and serum concentrations of VA and VE are correlated with PE risk. Methods A 1:1 matched case-control study was conducted to explore the association between the dietary intake and serum concentrations of VA and VE and the risk of PE in pregnant Chinese women. A total of 440 pregnant women with PE and 440 control pregnant women were included in the study. Dietary information was obtained using a 78-item semi-quantitative food frequency questionnaire. Serum concentrations of VA and VE were measured by liquid chromatography-tandem mass spectrometry. Results Compared with the lowest quartile, the multivariate-adjusted odds ratios [95% confidence interval (CI)] of the highest quartiles were 0.62 (95% CI: 0.40-0.96, P trend = 0.02) for VA, 0.51 (95% CI: 0.33–0.80, P trend =0.002) for β-carotene, and 0.70 (95% CI: 0.45–1.08, P trend = 0.029) for retinol. Additionally, for serum VA and VE concentrations, the multivariate-adjusted odds ratios (95% CI) were 2.75 (95% CI: 1.24–6.13, P trend = 0.002) and 11.97 (95% CI: 4.01–35.77, P trend < 0.001), respectively. No significant association was seen between VE intake and PE risk. Conclusions Dietary VA intake was negatively correlated with PE risk, and serum VA and VE concentrations were positively correlated with PE risk among pregnant Chinese women.